PENGETAHUAN, SIKAP DAN PRAKTIK GIZI GURU PAUD DIPERBAIKI DENGAN INTERVENSI e-HEALTH PEGIA - Purnamasari, Dyah Umiyarni; Briawan, Dodik; Kustiyah, Lilik; Tanziha, Ikeu; Hermadi, Irman (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Preschool teachers play a crucial role in influencing children's eating patterns at school, which is of utmost importance considering the detrimental impact of malnutrition on preschool children's cognitive abilities. In order to improve preschool teachers' nutrition behavior, it is imperative to provide education on nutritional behavior. One effective approach is implementing nutrition education for teachers through e-Health, which offers numerous advantages such as easier access and wider reach. Therefore, this research aimed to analyze the effectiveness of the Pegia eHealth intervention in improving the knowledge, attitudes, and practices of preschool teachers regarding nutrition. The sample consisted of 24 teachers from eight preschool centers in Purwokerto City, Indonesia. The e-Health intervention was conducted for 12 weeks, and the differences before and after the intervention were analyzed using the Wilcoxon test. The results showed a significant increase in the median knowledge by 12.00 with an interquartile range (IR) of 14.00, the median attitudes by 10.50 (IR: 8.75), and the median nutrition practices by 7.00 (IR: 3.00) (p-value < 0.05). The Pegia eHealth intervention showed its effectiveness in improving the nutrition knowledge, attitudes, and practices of preschool teachers.